International diversification of manufacturing operations: Performance implications and moderating forces - Lampel, Joseph; Giachetti, Claudio (Journal of Operations Management, 2013)
The strategic importance of diversifying international manufacturing for firms with global operations has been extensively documented in a series of studies. There is a lack of studies, however, of the performance implications of strategically spreading manufacturing operations across the globe. In fact, most research on international manufacturing to date has generalized from findings by researchers that examine international diversification at the level of the whole value chain, rather than specifically looking at the performance impact of dispersing production operations. Building on the concept of international manufacturing diversification, we show that its relationship with financial performance is inverted U‐shaped, and that this relationship is positively moderated by product diversification and co‐location of manufacturing and sales activities in the same geographic market. We place the development of international manufacturing diversification processes in the context of the resource based view and transaction costs economics. Hypotheses are tested using data on 38 firms with home base in 15 countries and car and light truck production activities in 45 countries from 2002 to 2008.